Saber social e desenvolvimento de software: avaliação crítica do modelo da fábrica de software - Leandra Leal (2008)
This paper address the problems of the organizational structure named "software factory" adopted by the company under analysis. This model utilizes alleged universal engineering methods, according to the fundamentals of industrial manufacturing, aiming to eliminate productivity issues and improve product quality. However, such methods have shown a trend of ineffective results rather than the expected quality improvement.The utilization of formal Software Engineering regulations and models "mutilates" the social and creative dimension of the information technology personnel and indicates a profound lack of knowledge regarding the means used by the analyst in the identification of user requirements, mainly those related to the innovative process. The empirical study based on the ergonomic analysis of the work performed by information technology analysts of a public services company demonstrates the importance of socialization in the work environment and the utilization of creative capacity in the development of higher quality software. The study has also disclosed that the reassignment of roles dictated by the "Software Factory" structure coupled with the outsourcing of software development has further aggravated the problems of the model previously utilized. The transfer of this activity to a remote location has generated difficulties regarding the relationship with business analysts and the integration with company operations. Under these conditions, the programmers have not been able to acquire the required knowledge for the development of products that meet user requirements.